Metacognitive Strategies and Deep Learning in EFL Reading Engagement: A Case Study - Erlidawati; Rahayu, Ririn; Rasyimah; Wahdaniah; Iqbal, Muhammad (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aims to explore the impact of the integration of metacognitive strategies and deep learning approaches on reading engagement of EFL students at IAIN Lhokseumawe. Using a qualitative case study design, the study involved 30 students of the English Language Study Program who were observed for 12 weeks. Data were collected through classroom observations, semi-structured interviews with 23 participants, and analysis of 90 student reflection journals. Data analysis was carried out thematically by triangulation to validate the findings. The results showed that the combination of metacognitive strategies (planning, monitoring, self-evaluation) and deep learning principles (inquiry-based learning and problem-solving) significantly increased reading engagement. Key findings include: (1) a 62% increase in the use of metacognitive strategies, (2) the transformation of interactions from mechanical to collaborative-critical, and (3) the internalization of strategies observed during the 12 weeks of the English Study Program, which occurred through three adaptation phases and were achieved in a span of 4 to 6 weeks. Implementation challenges such as infrastructure limitations and cultural resistance were successfully overcome through gradual scaffolding and contextual adaptation. This research provides practical contributions on innovative learning implementation models in resource-constrained environments, while simultaneously enriching the literature on contextual EFL pedagogy in Indonesia. The findings underscore the importance of a culturally sensitive approach in the implementation of Western learning strategies.